Cleaner Operations in Hotels: Recommendation for Post-Pandemic Green Recovery - Tiong Ying Ying; Stephen Laison Sondoh Jr; Geoffrey Harvey Tanakinjal; Oswald Aisat Iggau (2020)
Although the extant studies had examined the impact of green marketing, limited research has focused on green marketing as an attempt of cleaner production. This paper contributes to green marketing and cleaner production literature by introducing "clean service marketing" through adaptation of cleaner production onto the expanded green service marketing mix (people, physical evidence and process). The study further contributes to the literature by investigating the possible influence of clean service marketing in providing health value, enhancing social-quality performance and good differentiation advantage. The authors adopted a mixed-method study by systematic review and survey questionnaire to collect data. A systematic review was conducted to address the research question "Do firms' green approaches provide health value to its stakeholder? While 101 sets of questionnaire were distributed to the managers of the selected three-to-five stars hotel and resort in Malaysia to confirm the proposed hypotheses. Partial Least Square-Structural Equation Modeling was employed for quantitative data analysis, and SmartPLS 3.2.8 software was performed to analyze the data obtained. The results of the synthesis analysis addressed the research question that firms or any practitioners by going green could either improved human's health or perceived health. The result of the quantitative analysis revealed that only the green process is positively related to social-quality performance. In contrast, green people, green physical evidence and green process were found all positively related to differentiation advantage. With regards, the authors strongly recommend hotel and resort firms taking green as a "clean" approach for hotels' post-pandemic recovery.